Seeds, water, and markets to increase wheat productivity in Bihar, India - Kishore, Avinash; Singh, Vartika (Cereal Systems Initiative for South Asia, 2021)
Low and variable yields of wheat in the rice--wheat cropping systems of lower Indo-Gangetic Plains (IGP) of South Asia, covering Bihar and Eastern Uttar Pradesh (EUP) in India and the Terai region of Nepal, are a matter of significant concern for this densely populated region (Chatrath et al., 2007). Increasing the productivity and profitability of wheat is important for Bihar and E U P both for the income security of farmers and the food security of households (Keil et al., 2015). It is the second-largest crop in the region after rice in terms of area, production, and output value. Farmers in Bihar cultivate wheat on more than 2 million ha of land and produce 5--6 million tonnes of it every year. Wheat occupies 28% of the gross cropped area of Bihar and 70% of the sown area in the Rabi season. Despite its importance to the state’s agrarian economy and food security, wheat yields and the gross value of output per hectare are the lowest in Bihar among all major wheat-producing states of India while the cost of production (INR/tonne) is high (INR 10,630/tonne vs. INR 9,600/tonne for India); the net profit (INR per hectare) from wheat cultivation is also the lowest (Commission for Agricultural Costs and Prices (CACP), 2020). In this brief, we analyze the four major factors that contribute to low wheat yields in Bihar.